Biochars in the mitigation of greenhouse gases and on phosphorus removal and reuse - Novais, Sarah Vieira (2018)
Measures aimed at mitigating environmental impacts, especially the anthropic ones, are being progressively studied. Increasing greenhouse gases (GHG) emissions are among the biggest environmental problems in the world, with agriculture one of the major contributors to this impact. Water eutrophication from land misuse and agricultural systems also fits into such a scenario of concern. Biochar, the product of the pyrolysis of organic materials, appears as a recover of a list of environmental problems, among them the mitigation of GHG and the recovery of eutrophic or wastewater. In this sense, biochars of sugarcane straw (BCS) and poultry manure (BPM) were used in GHG emission tests in soils with contrasting textures. To do so, two pyrolysis temperatures (350 and 650 °C), three doses (12.5, 25 and 50 Mg ha-1), two texture classes (sandy and clayey) and two pH values (original pH and pH 5.5) were used. These same biochars were submitted to doping processes pre-pyrolysis with Mg2+ and post-pyrolysis with Al3+ for the adsorption of phosphorus (P). Desorption and adsorption experiments in competition with other anions by the exchange sites were done. The potential GHG mitigation of both biochars has been proven in the gas emission tests. The increase of the pyrolysis temperature (350 to 650 °C) further increases the gas mitigation, and the acidification of the original pH of the biochar causes a similar effect. The benefits of pyrolyzing such organic materials are best seen in sandy soil, with the production of biochar from these residues being an environmentally safe way of depositing these materials, at least with regard to the emission of GHG. Both biochars do not have P adsorption capacity without passing through chemical modification, and the doping process, with Mg or Al, granted this ability. The pre-doping process with Mg2+ generated a P maximum adsorption capacity (PMAC) of 250.8; 163.6; 17.7; 17.57 mg g-1 for the pyrolyzed BPM at 350 and 650 °C and for the BCS also pyrolysed at 350 and 650 °C, respectively. The post-doping process with Al3+ generated a PMAC of 701.6 and 758.9 mg g-1 for BPM and BCS, both of which were pyrolysed at 350 °C, respectively. The superior PMAC of the Al doped biochars was attributed to the fact that the cation that makes the bridge (Al3+) is trivalent, with high affinity for P. The high adsorption of Al by the biochars corroborates with such a statement. Both biochars, produced by the two doping processes, had a desorption of P around 80 % of the adsorbed value, allowing the inference that these products have the capacity to be used in nutrient reuse, mitigating another environmental problem: the use of the finite reserves of P. With the positive results coming from the pyrolysis of the materials in this thesis, we certify the biochar potential as a GHG mitigator, recovery for waters and a potential slow release fertilizer in P reuse.